ECONOMIC VALUE OF SEA GRAPES (Caulerva racemosa) IN MAPUR ISLAND, BINTAN PESISIR DISTRICT, KEPULAUAN RIAU PROVINCE - Ulfa, Suci Nurul; Amrifo, Victor; Warningsih, Trisla (Asian Journal of Aquatic Sciences, 2023)
The purpose of this study was to determine the economic value and benefits of sea grapes in Mapur Village, Bintan Pesisir District, Kepulauan Riau. This research was conducted in September 2021 in Mapur Village, Bintan Pesisir District, Kepulauan Riau. The method used was field observations and direct interviews with the local government and the community around Mapur Village. The results showed that the Mapur Village marine grape ecosystem has an area of 44,200 ha, and there are benefits to the value of the existence of IDR 208,896,000/year. Factors that influence the willingness to pay (WTP) of the community around the waters of Mapur Village in the form of the respondent's income level, the respondent's education level, the respondent's gender, the respondent's age, and the respondent's family dependents. With the benefits of the value of the existence of Mapur Village, it can be used as a basis for decision-making by the local government and the surrounding community in policy management and utilization of sea grapes in maintaining and preserving the distribution of sea grape ecosystems for future sustainability. With the results obtained in knowing the existence of the value function of a sea grape ecosystem, it can produce the formulation of sea grape conservation reserve areas in the waters of Bintan Pesisir, especially Mapur Village.